An Analysis of Anselm’s Philosophical Theology and the Problem of Man’s Freedom in His De Concordia - Tkachenko, Rostislav (Sententiae, 2015)
The purpose of this study is to discover, present and analyze the key ideas of Anselm of Canterbury concerning the notions of knowledge, will and mode of divine-human relations in the context of this “knowledge-will” framework which is important due to (a) somewhat insufficient attention to the medieval insights on the issue and (b) the peculiarity that Anselm’s intuitions have. More specifically, the object of the given paper is Anselmian understanding of relations between God’s foreknowledge and will, on the one side, and human free will, on the other side, as it is presented in the work entitled De Concordia. In this treatise Anselm of Canterbury partially uses and further elaborates some ideas of Augustine and Boethius, while integrating, updating and synthesizing them in a creative manner, and partially develops a number of thoughts of his own. As a result, there is a set of the well-formulated and comprehensive theses concerning (i) different types of (metaphysical) necessity, (ii) a proper definition of freedom of choice and will, (iii) the nature of will per se, and, finally, (iv) unique relation of “simultaneity” that exists between God’s knowledge, God’s will and the creature’s rational will. These ideas are presented and explicated in the article along with detailed exposition and analytical examination of the main line of argumentation found in the De Concordia.